(untitled) (World Economics and Finance Bulletin, 2024)
Inclusive leadership is one of the essential and necessary elements in managing institutions, especially under current conditions that require an increasing ability to grasp and deeply understand leadership-related concepts. Due to the importance of competent leadership in achieving the objectives and goals of institutions, there has been an urgent need for leadership with high efficiency. This research aims to explore the relationship between inclusive leadership and organizational commitment among employees within institutions, by studying a sample of employees in the Baghdad and National Iraqi banks. The research found a significant correlation between the dimensions of inclusive leadership and organizational commitment, where individuals’ commitment to their work is an indicator of how much they accept the values and goals of the organization they work for, as well as their strong desire and dedication to continuously strive to achieve those goals. This is based on the responses of the surveyed sample, which achieved the highest arithmetic mean with an average of 4.24